Sistemas cadastrais em diferentes contextos e a gestão do desenvolvimento rural: um diálogo possível? - Moreira, Diego Camelo (2019)
Rural development in its complexity can be interpreted in the political context through strategies and actions aimed at improving the living conditions of populations. In turn, the efficiency of such strategies is directly related to planning and information quality issues that support them. Brazil has a particular problem regarding the issue of territorial information for the rural, in the sense that there is a diversity of information systems that act in a disjointed manner in supplying the diverse demands of the social, economic, political, legal and environmental sectors throughout the country. In other countries these issues are already solved or in the process of consolidation such as Galicia, one of the Autonomous Communities of Spain. Given this scenario, this paper structures a set of discussions that help understanding the following question: How is the dialogue between information systems and the dimensions of rural development and how do they reflect in the consolidation of cadastral systems for rural areas in different contexts? Thus, there is a historical review of the processes and dynamics that influenced the implementation of rural land registry systems in Brazil and Galicia, as well as the organizational and technical dimensions that currently structure and shape the rural land registry systems in both contexts. This thesis is categorized as a multiple case study, with exploratory, descriptive and explanatory research and qualitative and quantitative approaches. That is, there is a combination of methodologies, as it aims at understanding and behavior of their objects of study, the territorial information systems for rural areas. This type of approach is called methodological triangulation or “mixed-methodology”. Due to the influence of the qualitative approach, the research methods used here have an inductive approach, in the sense that the dimensions and categories of interest will emerge concurrently with the processes of data collection and analysis of the information obtained. As a second case study, some information systems of the territory of Galicia are analyzed. This paper confirms the hypothesis that the cadastral systems analyzed do not act efficiently in the management of rural development, because they do not negotiate with social management. In turn, social management materializes through the articulation between government institutions and civil society organizations with clear rules that operationalize decision-making processes. In this sense, the link between land governance via consolidation of cadastral systems is evident. So that they become instruments to guarantee the legal certainty of proprietary rights, and guidance tools for public policies that qualify the integrated management of the territory (social, productive, economic and environmental aspects), and that minimize conflicts and power asymmetries, reflection of land demand.